2019
DOI: 10.3389/fphar.2019.00403
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Plantago asiatica L. Seeds Ameliorates Hypertension in Spontaneously Hypertensive Rats by Inhibition of Angiotensin Converting Enzyme

Abstract: Plantago asiatica L. seeds is a common folk medicine with a long history of medical use in China because of its antipyretic, diuretic, and expectorant properties. It has been applied to treat hypertension clinically due to its diuresis, however, its efficacy and mechanisms on anti-hypertension has not been reported yet to our knowledge. In this study, we investigated the antihypertensive effect and underlying mechanisms of P. asiatica L. seeds extract (PASE) in spontaneously h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Therefore, dietary supplements are preferred as alternatives to drugs in that they have fewer side effects and are easy to absorb. The antihypertensive effects of various natural extracts have been verified in vitro and in vivo [ 9 , 10 , 11 ]. These activities are associated with their flavonoids, terpenes, alkaloids, and phenolic acids [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dietary supplements are preferred as alternatives to drugs in that they have fewer side effects and are easy to absorb. The antihypertensive effects of various natural extracts have been verified in vitro and in vivo [ 9 , 10 , 11 ]. These activities are associated with their flavonoids, terpenes, alkaloids, and phenolic acids [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study compared the diuretic impact of CPS and SPS, which were observed to be different. Previous studies have also shown that phenylethanoid glycosides may have a blood pressure-lowering effect (Tong et al, 2019). Other studies have indicated that phenylethanoid glycosides have diuretic effects (Qi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent works have suggested that taking PS extracts (PSE) daily can regulate the severity of hypertension and thus may be potentially utilized as an antihypertensive herb ( Fu et al, 2019 ). Another study revealed that PSE improves hypertension in spontaneously hypertensive rats by disrupting the activity of angiotensin-converting enzymes (ACEs) ( Tong et al, 2019 ). In addition, we found that there is a relationship between the inhibition of ALD and AQP2 on the diuretic mechanism of PS.…”
Section: Discussionmentioning
confidence: 99%
“…In folk medicine, this plant can be used for curing several disorders, such as dysuria, edema, stranguria, eliminating heat from lungs, and improving phlegm. Also, it is declared that Plantaginis semen extract has been used for decreasing hypertension in Asian regions (Tong et al, 2019; Tzeng et al, 2016). According to modern pharmacological research, Plantaginis semen exerts specific functions in lowering blood lipid levels, declining blood pressure, and exerting antioxidative, immune regulatory, diuretic, anti‐inflammatory, and hypoglycemic properties (Pal et al, 2014).…”
Section: Plantaginis Semenmentioning
confidence: 99%